2017
DOI: 10.1139/cgj-2015-0532
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of dominant stress-transfer mechanisms in experimental debris flows of different particle-size distribution

Abstract: Physical modelling of debris flow in a small-scale flume has been carried out to investigate the internal stress-transfer mechanisms within unsteady, saturated, and segregating granular free-surface flows. Measurements of the internal velocity fields within model flows were obtained via planar laser-induced fluorescence and particle image velocimetry. Normalized velocity profiles taken at a section over the flow duration were found to essentially collapse onto a single curve, the shape of which was dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…The collapse of the profiles onto one indicates the similarity of the flow over this time frame, as also shown in other gravity-driven granular flows, e.g. [3,26,41]. The characteristics of experimental flows that are comparable to the current work are summarised in Table 1.…”
Section: Velocity Profilessupporting
confidence: 78%
See 2 more Smart Citations
“…The collapse of the profiles onto one indicates the similarity of the flow over this time frame, as also shown in other gravity-driven granular flows, e.g. [3,26,41]. The characteristics of experimental flows that are comparable to the current work are summarised in Table 1.…”
Section: Velocity Profilessupporting
confidence: 78%
“…The distinct shape of the velocity profiles for different experimental parameters lead to the definition of four different granular flow regimes that are relevant to debris flow bodies-immature, mature, plug flow and solid bed flow. These definitions have been frequently used to classify experimental debris flows conducted in more recent years [26,28,41]. Experimental debris flows are also often classified by directly comparing the internal velocity profiles with analytical profiles that are derived from simplified mathematical models with an assumed rheology [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Sanvitale and Bowman () found that well‐graded Duran glass particles flowing down a small‐scale flume form a plug flow type with high shear rates at the bottom and low velocity gradient at the top. Similarly, velocity profiles for natural sediment with a high content of fines showed the highest shear concentrated at the base in large‐scale rotating drum flows (Kaitna et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…First is through rheological approach and the other method is through coupled DEM/CFD analysis. In debris flows at the microscale, the particle dynamics involve exchange of momentum due to inertial granular collisions, friction between grains, viscous shear and solid fluid interactions (Iverson, 1997, Sanvitale andBowman, 2016). In general, the mobilized blocks during flows/rock falls move down the slope due to gravity with a subsequent impact and rebound (Ritchie, 1963, Paronuzzi, 1989).…”
Section: Introductionmentioning
confidence: 99%